Negotiating conflict and controversy in the early modern book world
1 online resource.
Keywords: The early modern European book world was confronted with many crises and controversies. Some conflicts were of such monumental scale that they wrought significant reconfigurations of the trade. Others were more quotidian in nature – evidence of the intensely competitive and at times predatory nature of the industry. How publishing negotiated and responded to the various crises, conflicts and disputes of the age is explored by the rich and varied interdisciplinary contributions in this volume. To succeed in the business of books, printers and publishers needed to seize the advantage in the often complex environments in which they operated. What was required was determination, resilience, and inventiveness, even in the most challenging of times.